Spin transport parameters in Ni80 Fe20/ Ru and Ni80 Fe20/ Ta bilayers - Gomez, Javier Enrique (2014)
We present a systematic study of the spin transport properties in two different bilayer systems, Ni80Fe20/Ru and Ni80Fe20/Ta, combining ferromagnetic resonance (FMR) and inverse spin Hall effect (ISHE) voltage measurements. We have estimated the effective spin mixing conductance g↑↓ by analyzing the permalloy (Py) thickness dependence of the FMR linewidth obtaining g↑↓=(3.8±0.7)×1015cm-2 and g↑↓=(1.3±0.4)×1015cm-2 for Py/Ru and Py/Ta, respectively. Analyzing the Ta thickness dependence of the ISHE voltage, we have been able to extract the spin diffusion length, λSD=1.5±0.5 nm, and spin Hall angle, ΘSH=-0.03±0.01, of Ta. From the two series of Py/Ta bilayers - with thickness variation of ferromagnetic and nonmagnetic layers, respectively - we demonstrate a path to estimate the spin diffusion length from the experimental data, independent of the spin Hall angle and the microwave field amplitude.